2016
DOI: 10.29121/granthaalayah.v4.i4.2016.2754
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee Production System, Challenges and Opportunities in Selected Districts of Gedeo Zone, Southern Nation, Nationalities and Peoples Regional State, Ethiopia

Abstract: The study was carried out in selected districts of Gedeo zones of southern Nation nationality and people’s regional state: such as Wonago, Kochere and DillaZuria/chichu/ districts. The objective of the study was to asses production systems, opportunities and constraints of apiculture farming in Gedeo zones of SNNPRs. Beekeeping is a long-standing practice in the study districts and appears as ancient history of the country as a whole. A cross sectional study, in which 90 households were purposively included an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 1 publication
2
10
1
Order By: Relevance
“…This is most probably because of poor extension services system, poor adoption of improved beekeeping technologies, high costs of beekeeping equipment. This result is partially in line with findings of Addis Getu and Malede Birhan (2014) [3] , Haftu Kebede and Gezu Tadesse (2014) [18] , Teklu Gebretsadik and Dinku Negash (2016) [29] , Welay Kiros and Tekleberhan Tsegay (2017), Abebe Mitikie (2017) [1] . They have stated that swarms catching are the main sources of honeybee colonies to start beekeeping in various parts of the country.…”
Section: N = Number Of Cases Se = Standard Error Of Meansupporting
confidence: 83%
See 1 more Smart Citation
“…This is most probably because of poor extension services system, poor adoption of improved beekeeping technologies, high costs of beekeeping equipment. This result is partially in line with findings of Addis Getu and Malede Birhan (2014) [3] , Haftu Kebede and Gezu Tadesse (2014) [18] , Teklu Gebretsadik and Dinku Negash (2016) [29] , Welay Kiros and Tekleberhan Tsegay (2017), Abebe Mitikie (2017) [1] . They have stated that swarms catching are the main sources of honeybee colonies to start beekeeping in various parts of the country.…”
Section: N = Number Of Cases Se = Standard Error Of Meansupporting
confidence: 83%
“…The zone has a total area of 10,000 km 2 and 2,954,136 total populations (of which 1,491,248 are males and 1,462,888 are females). When we see its land use features, the zone's total land falls in to the following categories: 48.70% cultivated, 2.29% forest, 5.04% shrub and bush land, 17.47% grazing land and 18% uncultivated land (Teklu G and Dinku N., 2016) [29] .…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Of the total production developing countries all to gather produce about 47% of the world total honey production. The major producers are China, Turkey, Argentina, Ukraine, Russian Federation etc [14]. Between 2001 and 2013, the total cumulative honey produced for some selected countries indicated that, China is the leading honey producing country followed by EU as indicated in (Figure 1).…”
Section: Ethiopia's Global Position In Honey and Beewax Productionmentioning
confidence: 97%
“…Ethiopia has the potential to produce 500,000 tons of bee honey annually. However, production has not surpassed 10% of that potential [53]. About 80% of the total honey produced in the country serves as raw material for producing Tej [54].…”
Section: Tejmentioning
confidence: 99%